The Islamic Worldview And Customary Law On Patterns Of Inheritance Division : Comparative Study Between Betawi and Minangkabau Communities - Shidiq Al-hakim; Unang Fauzi; Hendri Tanjung (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2023)
Background - This research investigates two crucial aspects of Indonesian culture, namely the inheritance division traditions in the Betawi and Minangkabau tribes, and how these traditions interact with the Islamic worldview. Research Methods - The research uses a qualitative approach, descriptive methods, and legal, sociological, and philosophical analyses to understand how the inheritance division traditions in these societies reflect the influence of the Islamic Worldview. Findings - The results show that both tribes retain elements of their distinctive culture in the division of inheritance, although the influence of Islam is visible in a number of aspects. Although there are differences with Islamic teachings in some respects, the principles of equality and justice remain an integral part of this tradition. Given the complexity of interpreting and implementing religious values in diverse cultural contexts, this research provides a deep insight into the interaction between Islam, adat and inheritance division in Indonesia. The findings of this study provide a basis for further comparisons with other cultural and religious contexts as well as practical implications for strengthening the principles of justice in inheritance systems in these societies.